Influence of concrete admixture on the bond strength of reinforced concrete submitted to high temperature - JERÔNIMO,V. A. (2020)
Abstract High temperatures can affect the macro and micro structural properties of reinforced concrete. This work aimed to analyze the bond strength behavior after high temperature exposure of two classes of concrete, the conventional 30 MPa and the high compressive strength 65 MPa concrete. The pullout test proposed by RILEM CEB / FIP RC6 (1983) was used for the evaluation of the compressive strength and modulus of elasticity. The influence of temperature on the physical-mechanical properties of concrete samples under a simulated fire situation was also studied for the evaluation of the resistant capacity in a post-fire situation. In addition to the analysis at 28 days, samples of the 30 MPa (group I) and 65 MPa (group II) classes were also investigated at 90 days exposed to room (23 °C), 400 °C and 800 °C temperatures. The bond strength curve was similar to that of compressive strength, where, at 400 °C, there was no statistical difference regarding room temperature and, at 800 °C, there was significant loss of strength in all cases. At 90 days age there was a loss of bond strength of 51 and 40 % for groups I and II, respectively. At 800°C the reductions were above 50 % in compressive strength and above 80 % in the modulus of elasticity, for both groups. These results show the structural impairment under high temperature. Comparing the test 28 and 90 days ages, there was no significant influence of age on the bond and compressive strength of the concretes.